2002
DOI: 10.1021/jp014180q
|View full text |Cite
|
Sign up to set email alerts
|

Electron and Hole Adducts Formed in Illuminated InP Colloidal Quantum Dots Studied by Electron Paramagnetic Resonance

Abstract: An electron paramagnetic resonance (EPR) study of photoexcited colloidal InP quantum dots (QD) shows the formation of electron and hole adducts. An EPR signal at g ) 0.58 is assigned to a nonradiative hole trap that does not form immediately upon illumination, but forms only after the illuminated sample ages and becomes stabilized at room temperature; it then becomes permanent at the InP QD surface. This signal completely disappears upon electron injection into the QD from a reducing agent (sodium biphenyl). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…However, for InP/ZnS-S QDs, a signal around a g factor of 2.006 immediately emerges after light irradiation. The absence of this signal in the dark indicates that it is highly related to the photogenerated exciton, rather than to the intrinsic structure defects or surface states of the QDs 62 . Careful examination further shows that it does not arise from photogenerated holes in InP QDs ( g = 2.001) 62 , 63 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for InP/ZnS-S QDs, a signal around a g factor of 2.006 immediately emerges after light irradiation. The absence of this signal in the dark indicates that it is highly related to the photogenerated exciton, rather than to the intrinsic structure defects or surface states of the QDs 62 . Careful examination further shows that it does not arise from photogenerated holes in InP QDs ( g = 2.001) 62 , 63 .…”
Section: Resultsmentioning
confidence: 99%
“…The absence of this signal in the dark indicates that it is highly related to the photogenerated exciton, rather than to the intrinsic structure defects or surface states of the QDs 62 . Careful examination further shows that it does not arise from photogenerated holes in InP QDs ( g = 2.001) 62 , 63 . Instead, it is probably due to electrons in the conduction bands of InP QDs (g = 2.006) according to the relevant literature 62 , 63 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the former in-situ EPR studies, trapping of electrons in the colloidal InP system upon optical excitation was reported. [70] Since the typical life times of such electron trapping events are rather short (in the order of 10 À 9 -10 À 3 s [71,72] ), long-life time (10 1 -10 2 s) radical spin traps such as 2,2,6,6-tetramethylpiperidin-1-yl) oxidanyl (TEMPO) or 5,5dimethyl-pyrroline N-oxide (DMPO) or metal cation dopants such as Mn 2 + were externally added to the analyzed samples to allow longer data acquisition times with a higher signal to noise ratio (S/N). [73][74][75] In the current in-situ X-band EPR measurements, no external spin-trap agents were added to the measured samples.…”
Section: Electron and Hole Trapping Analysis Of Cdse/cdsete Npl Via Ementioning
confidence: 99%
“…[24] The large surface:volume ratio of QDs allows dense surface traps to emit as brightly as the band-edge excitons, giving 'white light' QD emission. [22,25,26] While trap emission was initially attributed to surface indium dangling bonds, [27] more recent EPR [28] and XPS studies of HF-etched InP QDs evidence the role of hole-trapping P dangling bonds and surface oxidation. Ab-initio calculations [29], positron spectroscopy [30], XPS [31], and optical magnetic resonance [32] of CdSe QDs also show that surface traps stem from dangling selenium bonds (analogous effects found also for CdS QDs [33]).…”
mentioning
confidence: 99%